Pembuatan Produk Camilan Keripik Sehat dan Higienis Berbasis Daun Pepaya (Carica papaya L.) Di UPT Materia Medica Batu - Sholikha, Rizkia Ayu; Tiadeka, Pemta; Na’imah, Janatun (Universitas Muhammadiyah Gresik, 2019)
Usually, papaya leaf can be used as malaria disease treatment, prevent acne, appetite enhancer, milk supplement even making a toothache. In this research, papaya leaf is made as snack chips. The ingredients of papaya leaf’s chips are papaya leaf’s, rice flour, tapioca flour, red chili pepper, salt, eggs, guava leaf’s, clay, coriander, candlenut, flavorings, cooking oil, garlic, and water. The papaya chips also treat by organoleptic tests that consist of 5 criteria includes color, smell, texture, appearance, a taste of spices and moisture content test. The process of making papaya leaf’s chips include wash the papaya leaf, cutting, boiling used clay and guava then add salt to remove the bitter taste. The next step is making flour dough, frying, and slicing. The results of the organoleptic test 90% mean that consumers are very like papaya chips and the results of moisture content test are 4.564%.